Facilitating Teaching-learning Practices in Science - Koul, Anjni; Verma, Ruchi (SCHOOL SCIENCE, 2016)
The paper discusses the experiences with Class six students about teaching-learning the concept of ‘Reversible and non reversible changes’. The discussion depicts the classroom environment and involvement of students during teaching-learning process. The paper also highlights the effectiveness of activity based teaching-learning method for developing concepts in science. Activity based teaching–learning proved to be useful for the students especially at elementary level as it provides space to explore, observe, think, analyse and interpret. Authors have also shared their experiences related to integration of art with teaching-learning of science to make the process interactive, interesting and creative.